Work participation after receiving multidisciplinary treatment or acceptance and commitment therapy intervention for return to work: long-term follow-up of a randomized controlled trial among sick-listed individuals with mental disorders and/or chronic pain - Erik Berglund; Ingrid Anderzén; Magnus Helgesson; Per Lytsy; Åsa Andersén (BMC Public Health)
Abstract Background The return-to-work (RTW) process for individuals on long-term sick leave can be complex. Vocational rehabilitation may facilitate RTW; however, many intervention studies often have relatively short follow-up periods. The purpose of this study was to assess long-term work participation 2–7 years after the initiation of a three-armed randomized controlled trial aimed at RTW for individuals on long-term sick leave because of mental disorders and/or chronic pain. Methods This study followed 220 participants out of 402 (response rate 55%, 205 female) who had previously participated in a randomized controlled trial. They were allocated to one of three groups: multidisciplinary team assessment and individualized treatment (MDT), acceptance and commitment therapy (ACT) or a control group. The participants were followed up at two, three, four, five, six, and seven years after inclusion. The outcome, work participation, was assessed using registry data and defined as having the main source of annual income from paid work during the follow-up years. Results Participants in the MDT intervention group were, to a larger extent, in paid work during follow-up in years four (9.0% points), five (2.5% points), six (7.6% points), and seven (4.1% points) after inclusion, compared to the control group. Participants in the ACT intervention group were, to a larger extent, in paid work during follow-up in years four (14.8% points), six (17.6% points), and seven (13.9% points) after inclusion, compared to the control group. Conclusion This study, primarily involving female individuals on long-term sick leave, suggests that both MDT and ACT interventions can improve long-term work participation. The results also indicate some time-lag effect of the interventions. Trial registration The original randomized study was registered at the Clinicaltrials.gov Register Platform (ID NCT03343457); registered on November 15, 2017 (retrospectively registered).